Research On The Relationship Between Total Quality Management Practices And Firms Performance - Hua, Pan Xin (2008)
This study dicusses about improving quality level of products and then to improve their performance by total quality management. The aim of this study is to examine the relationship between total quality management (TQM) practices and firm performance, and then identify which elements of TQM are the best predictors of firm performance .